PENGARUH MODEL LATIHAN TEACHING GAMES FOR UNDERSTANDING TEHADAP KEMAMPUAN BERMAIN FUTSAL - Bukari, Bukari; Gustian, Uray; Samodra, Touvan Juni (Universitas Tanjungpura, 2023)
Futsal is a sport that requires a lot of basic technical skills. One sport that really requires the ability to play futsal skills. The ability to play is one way how a player is able to master the game. By improving the basic techniques, adjustments and support in the game.. So that when you control the ball it is less effective to control it. So for that in need of directed and appropriate training. One of them is playing practice, so that players don't get bored while doing practice. A good training model is the Teaching Game for Understanding (TGfU) training model. The purpose of this research is to find out how effective the effect of the Teaching Game for Understanding training model is on the ability to play futsal. This research method uses the experimental method